2021
DOI: 10.1111/jfpp.15369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fractionation on fatty acids composition, phenolic compounds, antioxidant characteristics of olein and super olein fractions of flaxseed oil

Abstract: Flaxseed oil was fractionated at −40°C, filtrate was designated as olein fraction (31% yield), which was further fractionated at −60°C, and filtrate was named as super olein fraction (17% yield). Flaxseed oil, olein, and super olein fractions were stored at 25°C–30°C for the duration of 90 days. Alpha linolenic acid in flaxseed oil, olein, and stearin fraction was 55.26%, 63.47%, and 71.61%. High‐performance liquid chromatography (HPLC) characterization showed that phenolic compound was concentrated in olein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Chia oil, its olein, and stearin fractions were characterized by phenolic compounds, and OF showed the highest content of phenolic compounds followed by chia oil and stearin fraction (Ullah et al, 2016). Azad et al (2021) produced OF and SOF from flaxseed oil, and the same were characterized for phenolic compounds on HPLC, it was reported that phenolic compounds were concentrated in OF and SOF flaxseed oil. OF and SOF of palm oil showed more content of phenolic compounds than substrate palm oil (Kumar & Krishna, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chia oil, its olein, and stearin fractions were characterized by phenolic compounds, and OF showed the highest content of phenolic compounds followed by chia oil and stearin fraction (Ullah et al, 2016). Azad et al (2021) produced OF and SOF from flaxseed oil, and the same were characterized for phenolic compounds on HPLC, it was reported that phenolic compounds were concentrated in OF and SOF flaxseed oil. OF and SOF of palm oil showed more content of phenolic compounds than substrate palm oil (Kumar & Krishna, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The higher induction period of OF and SOF of date seed oil was due to the presence of antioxidant substances in higher concentrations; further, the lower induction period of winterized sunflower, soybean, canola, cotton seed, and safflower oils was due to the loss of tocopherols and other antioxidant compounds during refining and bleaching, etc. The induction period of OF and SOF of date seed oil was determined on Rancimat, parent flaxseed seed had the highest induction period followed by OF and SOF, respectively (Azad et al, 2021). Ullah et al (2016) described that the induction period of OF of chia oil was lower than parent chia oil and its stearin fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The phospholipid content was significantly influenced by technological methods applied during oil extraction. 8 Triglycerides and fatty acid profiles of oils and fat can be modified to a great extent by technological methods or fat modification strategies such as chemical/ enzymatic interesterification, transesterification, blending, and low-temperature crystallization/winterization/fractionation. Among the listed techniques, low-temperature crystallization/ fractionation is one of the most commonly used methods as versions of oils and fat modified by this method can be used in the production of traditional foods and the development of functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Among the listed techniques, low-temperature crystallization/ fractionation is one of the most commonly used methods as versions of oils and fat modified by this method can be used in the production of traditional foods and the development of functional foods. 8 Modification of fats can be achieved via solvent and low-temperature crystallization; however, the latter is more suited for the food industry as the fats and oils modified by the former method may have residues of hazardous solvents used for fractionation. 9 Hussain et al 10 produced olein and super-olein fractions of date seed oil by the dry crystallization method.…”
Section: Introductionmentioning
confidence: 99%